Shared Service Centre implementation & benefits in South Africa - Wilson, Andrew (My University, 2014)
The context of this research is to review the process companies adopt when deciding to implement a shared service and whether shared services add value. The report establishes what business processes are adopted during the implementation of a Shared Service Centre (SSC) and what financial benefits are realised. SSC’s are a method to provide back-office functions to internal customers at lower costs and higher quality than they experience at present. They have cost, service, and strategic advantages (Mechling 2007). The problem researched in this study was to analyse and evaluate the process companies adopt when implementing a SSC and determine the value of its economic and operational contributions to these companies. This study uses a qualitative methodology to answer the research questions. Qualitative methodology is defined as “participatory knowledge claims, narrative design, and openended interviewing (Creswell 2009). The key findings from the research was that SSC’s requires identification, mobilisation, consolidation, extraction and encapsulation with respect to the process adopted during implementation of the SSC and a strong synergy has been drawn back to literature. Another key finding is with respect to determining economic benefits through the operations of a SSC, is that the companies that adopted the shared service model benefited by reduced costs, improved service and provided strategic advantages. Lastly, the key message from the research is that SSC’s have benefits as far as costs are concerned and that certain best practices are identified with regards to implementing SSC’s. There is still further research required as far as some of the bi-products of SSC’s are concerned, however this was not covered in the scope of this research.
MBA thesis
Keywords: Shared service centres